2020
DOI: 10.3390/microorganisms8121941
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Wet Market Modernization Levels and Hygiene Practices on the Microbiome and Microbial Safety of Wooden Cutting Boards in Hong Kong

Abstract: Accessing food through wet markets is a common global daily occurrence, where fresh meat can be purchased to support an urbanizing world population. Similar to the wet markets in many other metropolitan cities in Asia, Hong Kong wet markets vary and are characterized by differing hygiene routines and access to essential modern technologies. The lack of risk assessments of food contact surfaces in these markets has led to substantial gaps in food safety knowledge and information that could help improve and main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Moreover, these informal marketplaces are more sustainable, as they reduce transport and limit waste and the amount of packaging. It is surely important to consider that, in each form of food product trade, hygienic practices must be guaranteed and implemented to ensure food safety and public health [114]. Moreover, there are also more and more examples of food production in the urban context that are contributing to shortening the food supply chain [115].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these informal marketplaces are more sustainable, as they reduce transport and limit waste and the amount of packaging. It is surely important to consider that, in each form of food product trade, hygienic practices must be guaranteed and implemented to ensure food safety and public health [114]. Moreover, there are also more and more examples of food production in the urban context that are contributing to shortening the food supply chain [115].…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, thanks to public health awareness, significant efforts have been made towards improving the safety and quality of processed fresh meats in these wet markets [ 1 , 2 ]. Nevertheless, despite the increase in food safety awareness, wet markets have repeatedly been identified as epicenters of potential public health hazards [ [3] , [4] , [5] , [6] , [7] ], primarily biological hazards.…”
Section: Introductionmentioning
confidence: 99%
“…Wet markets are densely populated hubs characterized by a large influx of customers and regulated or unregulated meats, and the hygiene level of the wooden cutting boards used to process these meats remains poorly described. Previous reports from Hong Kong wet markets noted a significant breach in cleaning standards meant for wooden cutting boards, in which surface scraping was used in most studied cases as a traditional cleaning technique [ 5 , 15 ]. Further analyses revealed that these hygienic practices were incapable of guaranteeing proper surface hygiene.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations